Pengembangan Aplikasi berbasis Mobile untuk Pelaporan Ancaman Kejahatan di Perumahan Panorama Cibodas - Syarief Noor Permadi; Issa Arwani; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Panorama Cibodas Residence is the author's residence located at Jalan Prabu Kian Santang, Kelurahan Sangiang Jaya, Kecamatan Periuk, Kota Tangerang. Based on direct observations by the author, Panorama Cibodas Residence has 3 security officers who carry out shift tasks in 3 shift, so that in 1 shift there is only 1 security officer on guard. The only 1 person security certainly will not be able to carry out whole residential area. If a crime occurs far from a security post, then it can't be dealt directly by security officers. So to maintain security at Panorama Cibodas Residence environment need help from the residents. In this research, the authors developed SKIP (Sistem Keamanan di Perumahan) application to report threats of crime in the Panorama Cibodas environment by developing Prototyping method to help residents maintain security in the Panorama Cibodas Residence. The prototype development method was chosen because the author's previously proposed the functional requirements of the application in the form of a prototype and then were shown to residents to get feedback until they got the final functional needs. Tests conducted on the SKIP (Sistem Keamanan di Perumahan) application is validation testing (blackbox), usability testing and compatibility testing. In validation testing results is 100% success rate. In usability testing results is 100% success rate for task execution by the respondent and has a final score on the System Usability Scale (SUS) 80 which falls into the grade B and adjectiva rating â€œgoodâ€ category. In compatibility testing, SKIP application can run well on manual testing device and in automatically testing with Firebase Test Lab on the Android operating system version of minimum KitKat 4.4 with level API 19 and maximum Pie 9.0 with level API 28.